Revolution Day : The Human Story of the Battle for Iraq - Omaar, Rageh (GHQ, Rawalpindi Army Publishing House, 2008)
The human story of the battle of Iraq in 2003 from the perspective of the BBC news correspondent, Rageh Omaar, who had spent several years living and reporting from Iraq before the war. He describes the atmosphere before the bombardment of Baghdad began and how the populous coped.
Include Maps and Index
Keywords: Iraq -- Iraq War (2003-2011) -- Iraq--Baghdad -- Social aspects